Прикметники на позначення простору в сучасній англійській мові: системні та семантичні особливості - Канонік, Наталія Петрівна; Kanonik, N. P. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Cтаттю присвячено дослідженню семантичної структури прикметників на позначення простору в сучасній англійській мові. У результаті кількісного аналізу та за критерієм семантичного змісту виокремлено ядерні та периферійні лексеми на позначення простору за долею семи просторовості, за допомогою компонентного аналізу виділено сім лексико-семантичних груп просторових прикметників, окреслено семантичну структуру досліджуваних лексем й описано системний та семантичні особливості просторових прикметників. The article devotes to the investigating the semantic structure of the adjectives denoting space in Modern English. The actuality of the researched microsystem is determined by the importance of the detonate space as a fundamental cate¬gory of human mind, the necessity to reveal the systemic character of the lexical organization in the English vocabulary. Due to the complex methology the systemic character of the researched lexical units has been displayed. In the result of the componential analysis and with the criterion of the semantic content the kernel and the periphery lexical units have been singled out, 7 lexico-semantic groups of spacious adjectives have been registered, the semantic structure of the investigated lexemes has been outlined, the systemic and the semantic peculiarities of the spacious adjectives have been described. The analysis of the semantic structure of the spacious adjectives has proved the fact about the availability of more than one semantic feature.
Adjectives Denoting Space in Modern English: Systemic and Functional Peculiarities
Keywords: простір; space; просторовість; spaciousness; мікрополе; microfield